1960
DOI: 10.4141/cjps60-096
|View full text |Cite
|
Sign up to set email alerts
|

Economic Losses Caused by Weed Competition in Manitoba Grain Fields: Ii. Effect of Weed Competition on the Protein Content of Cereal Crops

Abstract: Economic losses caused by weed competition in Manitoba grain crops were studied on 142 farm fields during a 3-year period, 1956 to 1958 inclusive. Ten paired plots were located in each farm field, one-half of each paired plot being kept weed-free throughout the growing season. Per cent protein was determined on wheat, barley and oat samples collected from 60 of these farm fields. Significant increases in protein content were obtained following weed removal in 22 of the 60 grain fields studied and small increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Protein content of wheat and bailey seeO may be decreased (Friesen et al 1960) or unaffected (Bell and Nalewaja 1968b (Baum 1968). Mason (1853) stated that oats were cultivated in Newfoundland in 1622, according to Coffman (1961), and wild oats occurred as an impurity in the grain.…”
mentioning
confidence: 99%
“…Protein content of wheat and bailey seeO may be decreased (Friesen et al 1960) or unaffected (Bell and Nalewaja 1968b (Baum 1968). Mason (1853) stated that oats were cultivated in Newfoundland in 1622, according to Coffman (1961), and wild oats occurred as an impurity in the grain.…”
mentioning
confidence: 99%
“…The increase in percentage grain N, hence grain protein content, in the 1989 spring barley and 1990 spring wheat crops, suggests that weeds reduce the crop's ability to take up and utilize N. Friesen et al (1960) found significant increases in grain protein following weed removal in several of the crops they studied. They concluded that weeds compete very effectively with grain crops for available N and that reductions in grain yield resulting from weed competition are generally accompanied by reductions in protein content as well.…”
Section: Grain Proteinmentioning
confidence: 83%
“…It can be observed that it increases with the rate of nitrogen fertilizer. However, the use of herbicide did not cause any change in the levels of grain N. Nevertheless, since the weight of the wheat grain significantly increased as a result of using the herbicide, protein production per area increased, bearing out Friesen et al (2).…”
Section: Figure 1 ¿Hows the Time Course Of The Mean Concentration Of mentioning
confidence: 86%